Methodology for Conducting Practical Classes in Physics Through the Design Method (Eurasian Journal of Engineering and Technology, 2023)
The article outlines the methodology for conducting practical classes in Physics in technical higher education institutions through the method of design of objects of professional activity. In this case, a clear example is given of the specifics of the design method itself, the stages of its organization and its direct application in the preparation of specialists in the field of architecture and construction.